Polylactic acid resin composition and use thereof

CN123004101APending Publication Date: 2026-10-30ADVANCED SEMICON ENG INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610953441.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-11-01
Filing Date
2018-10-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

PPE类IC托盘在燃烧之后可释放温室气体并且对环境造成破坏

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a polylactic acid resin composition and use thereof. A polylactic acid resin composition comprising about 100 parts by weight of a polylactic acid resin, about 0.001 to about 3 parts by weight of a nucleating agent, and about 3 to about 70 parts by weight of a filler. The polylactic acid resin composition can be processed into a biodegradable molded article or other products having high impact strength and high heat distortion temperature.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Information related to divisional application

[0002] This application is a divisional application of the invention patent application filed on October 22, 2018, with application number "201811227524.9" and invention title "Polylactic Acid Resin Composition and Its Application". Technical Field

[0003] This invention relates to a biodegradable polylactic acid resin composition and its applications. Background Technology

[0004] In recent years, plastics made from natural plant materials have received increasing attention due to global warming. Polylactic acid (PLA) resin is biodegradable and available from renewable resources such as corn starch, making it an environmentally friendly polymer. However, PLA resin is known to have poor physical properties, such as low heat resistance, poor surface resistivity, and poor mechanical properties. Furthermore, PLA resin exhibits a low crystallization rate and low crystallinity, which may result in products formed from PLA potentially lacking sufficient heat distortion temperature (HDT) and impact strength. Therefore, PLA resin is difficult to utilize in electronic applications, such as integrated circuit (IC) trays. There is a desire to improve the properties of PLA to expand its applications in the IC field.

[0005] IC trays are used to hold, handle, and transport IC packages. Suitable IC trays for manufacturing processes such as reflow soldering and IC shipping require several specific characteristics, such as high HDT (highest hardness), impact strength, surface resistivity, and other properties. Currently, there is still a need for an environmentally friendly IC tray with these required characteristics. Typical IC trays are primarily made of polyphenylene oxide (PPE), a petrochemical product that is not biodegradable in normal environments. PPE-based IC trays can release greenhouse gases and damage the environment when burned. Therefore, an environmentally friendly IC tray with high HDT, high impact strength, and low surface resistivity is needed. Summary of the Invention

[0006] In some embodiments, the present invention provides a polylactic acid (PLA) resin composition comprising about 100 parts by weight of PLA resin; about 0.001 to about 3 parts by weight of nucleating agent, based on about 100 parts by weight of PLA resin; and about 3 to about 70 parts by weight or about 3 to about 50 parts by weight of filler, based on about 100 parts by weight of PLA resin. The present invention also provides a tray for use in electronic components formed from a resin composition of some embodiments of the present invention. The present invention further provides a biodegradable molding article formed from a resin composition of some embodiments of the present invention.

[0007] In some embodiments, the present invention further provides a tray for use with electronic components. The tray for use with electronic components comprises about 100 parts by weight of PLA resin; about 0.001 to about 3 parts by weight of nucleating agent based on about 100 parts by weight of PLA resin; and about 3 to about 70 parts by weight or about 3 to about 50 parts by weight of filler based on about 100 parts by weight of PLA resin.

[0008] In some embodiments, the present invention also provides a biodegradable molding article. The biodegradable molding article comprises about 100 parts by weight of PLA resin; about 0.001 to about 3 parts by weight of nucleating agent, based on about 100 parts by weight of PLA resin; and about 3 to about 70 parts by weight or about 3 to about 50 parts by weight of filler, based on about 100 parts by weight of PLA resin. Detailed Implementation

[0009] Polylactic acid

[0010] In some embodiments of the present invention, polylactic acid (PLA) may be a homopolymer of lactic acid. Lactic acid exists as optical isomers, namely L-lactic acid (L-form) and D-lactic acid (D-form). In some embodiments of the present invention, PLA may be prepared from one or both of the optical isomers. This is done to obtain a high melting temperature (T0). m ) and high glass transition temperature (T g The purpose of the PLA is to use one of the aforementioned optical isomers as a major component. For example, in the PLA, the content of the L-form of lactic acid may be not less than about 80 mol% or not more than about 20 mol%; or in the PLA, the content of the L-form of lactic acid may be not less than about 85 mol% or not more than about 16 mol%; or in the PLA, the content of the L-form of lactic acid may be not less than about 90 mol% or not more than about 12 mol%, with the remainder corresponding to or including the D-form of lactic acid.

[0011] In other embodiments of the invention, PLA may be a copolymer of lactic acid and a hydroxycarboxylic acid component other than lactic acid. The hydroxycarboxylic acid component other than lactic acid may be, for example, glycolic acid, hydroxybutyric acid, hydroxyvaleric acid or hydroxypentanoic acid, hydroxyhexanoic acid or hydroxyheptanoic acid.

[0012] PLA can be formed by polycondensation using the aforementioned monomers or by ring-opening polymerization using the corresponding cyclic dimers or compounds of the aforementioned monomers (e.g., lactide, which is a cyclic dimer of lactic acid).

[0013] In some embodiments of the present invention, the weight-average molecular weight (M) of PLA is... wThe weight-average molecular weight of PLA can be at least any one of the following: about 10,000 g / mol, about 20,000 g / mol, about 30,000 g / mol, about 40,000 g / mol, and about 50,000 g / mol; and can be at most any one of the following: about 160,000 g / mol, about 200,000 g / mol, about 250,000 g / mol, about 300,000 g / mol, about 400,000 g / mol, and about 500,000 g / mol. For example, the weight-average molecular weight of PLA can be from about 30,000 g / mol to about 250,000 g / mol.

[0014] [Nucleating agent]

[0015] In some embodiments, nucleating agents can be used to improve the nucleus arrangement of PLA crystals and increase the crystallization rate and crystallinity of PLA. Increasing the crystallization rate and crystallinity of PLA can increase HDT and impact strength. In some embodiments of the invention, nucleating agents that can improve the crystallization rate and crystallinity of PLA can be used in resin compositions. In some embodiments, the nucleating agent comprises a metal carbonate (e.g., an alkaline earth metal carbonate, such as calcium carbonate or barium carbonate), an ester derivative of citric acid (e.g., acetyltributyl citrate), a metal silicate (e.g., hydrated magnesium silicate, such as talc), an amino acid (e.g., glycine or L-alanine), a poly(amino acid) (e.g., polyglycine), a heterocyclic organic compound (e.g., N-aminophthalimide), a metal oxide (e.g., titanium dioxide), or a combination of two or more thereof. In some embodiments, the nucleating agent is L-alanine.

[0016] In some embodiments of the invention, the nucleating agent may be added to the PLA resin composition in amounts of about 0.001 to about 3 parts by weight, based on about 100 parts by weight of PLA resin; for example, in amounts of about 0.001, about 0.005, about 0.01, about 0.05, about 0.1, about 0.5, about 1, about 1.5, about 2 or about 3 parts by weight, based on about 100 parts by weight of PLA resin.

[0017] [Filler]

[0018] Fillers can be added to resin compositions for a variety of purposes, such as reducing costs, improving mechanical strength, or adjusting the appearance of the final product. Different fillers are selected for different purposes. It has been found that some fillers may be advantageous to one property of the resin composition but disadvantageous to another. In addition, the addition of fillers such as rubber and plasticizers may adversely affect the thermal stability of the resin composition.

[0019] In some embodiments of the invention, the filler suitable for the PLA resin compositions of the invention comprises an inorganic filler (e.g., glass fiber or crystalline silicon), a carbon-containing filler (e.g., in the form of carbon fibers or particles, such as carbon fibers or carbon black), or any combination of two or more thereof. In some embodiments, the filler comprises carbon fibers, carbon black, or both. In other embodiments, the filler comprises carbon fibers. It has been found that adding such fillers to the PLA resin compositions of some embodiments of the invention can significantly improve the mechanical properties of PLA, particularly impact strength, and further increase HDT. Due to the synergistic effect of the nucleating agent and the filler, the resulting PLA product exhibits excellent mechanical and thermal properties, including a high HDT of about 134°C or higher (measured according to ASTM D-648 at a load of 264 psi) and an impact strength of about 1.5 kg-cm / cm or higher.

[0020] In some embodiments, fillers, such as carbon fibers, carbon black, or crystalline silicon, may also reduce the surface resistivity of the PLA resin composition so that the resulting PLA product is antistatic.

[0021] Fillers with a variety of suitable lengths and / or diameters can be used. In some embodiments, the length (e.g., average length) of the filler (such as carbon fiber) is from about 0.01 mm to about 800 mm, for example, about 0.01 mm, about 1 mm, about 10 mm, about 50 mm, about 100 mm, about 200 mm, about 300 mm, about 400 mm, about 500 mm, about 600 mm, about 700 mm, or about 800 mm. In some embodiments, the diameter (e.g., average diameter) of the filler (such as carbon black or carbon fiber) is from about 0.01 μm to about 100 μm, for example, about 0.01 μm, about 1 μm, about 10 μm, about 20 μm, about 30 μm, about 40 μm, about 50 μm, about 60 μm, about 70 μm, about 80 μm, about 90 μm, or about 100 μm.

[0022] Fillers can be added to PLA resin compositions in varying appropriate amounts, as long as they can produce a synergistic effect with the nucleating agent. In some embodiments, fillers are added to PLA resin compositions of some embodiments of the invention in amounts from about 100 parts by weight of PLA resin, such as about 3, about 5, about 10, about 15, about 20, about 25, about 30, about 35, about 40, about 45, about 50, about 55, about 60, about 65, or about 70 parts by weight of PLA resin. In some embodiments, fillers are added to PLA resin compositions in amounts from about 100 parts by weight of PLA resin, such as about 3 to about 50 parts by weight, about 5 to about 50 parts by weight, or about 5 to about 30 parts by weight of PLA resin. If the filler content is insufficient, the effect of the filler may not be significant. If the filler content is too high, it may lead to poor filler dispersion and even filler agglomeration. Both of these situations can reduce the conductivity of PLA resin and affect its antistatic properties.

[0023] [Coupled agent]

[0024] In some embodiments of the PLA resin compositions of the present invention, PLA is an organic material, while the filler is an inorganic material. Unlike organic materials, which can form bonds with each other through functional groups, inorganic materials typically do not form strong bonds with organic materials, potentially resulting in poor compatibility and adhesion between PLA and the inorganic filler. To address this issue, coupling agents can be used to modify the surface of the inorganic filler, and the inorganic filler can be bonded to the organic material via the dual reactivity of the coupling agent. Coupling agents can also be used with organic fillers to further improve the compatibility and adhesion between PLA and the organic filler. In some embodiments, the filler is bonded to PLA via a coupling agent (e.g., covalently).

[0025] The coupling agent may be a silane coupling agent, a titanate coupling agent, or a combination thereof. A variety of suitable silane coupling agents and titanate coupling agents can be selected. Examples of silane coupling agents suitable for some embodiments of the present invention include, but are not limited to, trimethoxysilane, triethoxysilane, or combinations thereof. According to some embodiments of the present invention, the silane coupling agent may be 3-acryloyloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, or combinations thereof. Examples of titanate coupling agents suitable for some embodiments of the present invention include, but are not limited to, titanium di(cumylphenylate)oxyacetate, di(dioctylphosphato)ethylene titanate, or combinations thereof.

[0026] The coupling agent can be added to the PLA resin composition in varying appropriate amounts, and this amount can be adjusted depending on the filler content. In some embodiments, the coupling agent can be added to the PLA resin composition in amounts from about 0.001 to about 5 parts by weight, for example, about 0.001, about 0.005, about 0.01, about 0.05, about 0.1, about 0.5, about 1, about 2, about 3, about 4, or about 5 parts by weight, based on about 100 parts by weight of PLA resin.

[0027] [Polylactic acid resin composition]

[0028] In some embodiments of the present invention, the PLA resin composition can be prepared by a variety of suitable methods. In some embodiments, the PLA resin composition is prepared by: (1) mixing PLA resin with a nucleating agent to form a first mixture, (2) mixing a filler and a coupling agent to form a second mixture, and (3) adding the second mixture to the first mixture (or otherwise combining the first mixture with the second mixture) to prepare the PLA resin composition.

[0029] PLA resin compositions can be further processed into end products such as caps for electronic products (e.g., mobile phones or computers), food containers or trays, or trays for industrial components. In some embodiments, the PLA resin composition can be kneaded using a twin-screw extruder and subsequently injected using an injection molding machine at a temperature range of about 150°C to about 200°C to form a tray. The tray can be further baked to release stress and stabilize the tray size.

[0030] Products made from PLA resin compositions according to some embodiments of the present invention are biodegradable, meaning they can be decomposed in the natural environment, for example, by microorganisms. In some embodiments, the PLA resin composition can decompose to about 70 wt% or more in the natural environment within about 90 days.

[0031] In some embodiments, the PLA resin composition is processed into a tray. In other embodiments, the tray has an impact strength of about 1.5 kg-cm / cm or higher (e.g., about 1.55 kg-cm / cm or higher, about 1.6 kg-cm / cm or higher, about 1.65 kg-cm / cm or higher, about 1.7 kg-cm / cm or higher, about 1.75 kg-cm / cm or higher, about 1.8 kg-cm / cm or higher, about 1.85 kg-cm / cm or higher, or about 1.9 kg-cm / cm or higher, and can be up to about 1.95 kg-cm / cm or higher); an HDT of about 125°C or higher (e.g., about 130°C or higher, about 135°C or higher, about 140°C or higher, about 145°C or higher, or about 150°C or higher, and can be up to about 155°C or higher); and a surface resistivity of about 10 Ω·cm. 12 ohm / sq or less (e.g., about 10 ohms / sq) 11 ohm / sq or less, approximately 10 10 ohm / sq or less, approximately 10 9 ohm / sq or less, approximately 10 8 ohm / sq or less, approximately 10 7 ohm / sq or less, approximately 10 6 ohm / sq or less, approximately 10 5 ohm / sq or less or about 10 4 ohm / sq or less, and can be as low as about 10 3 (ohm / sq or less). Trays, such as IC trays, are suitable for the electronics industry and are specified for high HDT, high impact strength, and low surface resistivity (e.g., HDT of about 125°C or higher, impact strength of about 1.5 kg-cm / cm or higher, and surface resistivity of about 10 ohms / sq or less). 12 ohm / sq or less).

[0032] In some embodiments, the PLA resin composition is processed into a biodegradable molding article. In other embodiments, the biodegradable molding article has a decomposability of about 70 wt% or higher in the natural environment after about 90 days. In other embodiments, the biodegradable molded article has an impact strength of about 1.5 kg-cm / cm or higher (e.g., about 1.55 kg-cm / cm or higher, about 1.6 kg-cm / cm or higher, about 1.65 kg-cm / cm or higher, about 1.7 kg-cm / cm or higher, about 1.75 kg-cm / cm or higher, about 1.8 kg-cm / cm or higher, about 1.85 kg-cm / cm or higher, or about 1.9 kg-cm / cm or higher, and can be as high as about 1.95 kg-cm / cm or higher); an HDT of about 125°C or higher (e.g., about 130°C or higher, about 135°C or higher, about 140°C or higher, about 145°C or higher, or about 150°C or higher, and can be as high as about 155°C or higher); and a surface resistivity of about 10 Ω·cm. 12 ohm / sq or less (e.g., about 10 ohms / sq) 11 ohm / sq or less, approximately 10 10 ohm / sq or less, approximately 10 9 ohm / sq or less, approximately 10 8 ohm / sq or less, approximately 10 7 ohm / sq or less, approximately 10 6 ohm / sq or less, approximately 10 5 ohm / sq or less or about 10 4 ohm / sq or less, and can be as low as about 10 3 (ohm / sq or less). The biodegradable molded articles are suitable for the electronics industry and are specified to have high HDT, high impact strength and low surface resistivity (e.g., HDT of about 125°C or higher, impact strength of about 1.5 kg-cm / cm or higher and surface resistivity of about 10 ohms / sq or less). 12 ohm / sq or less).

[0033] Example

[0034] Some embodiments of the invention will now be further explained with reference to the following working examples and comparative examples; however, these examples do not limit the scope of the embodiments of the invention. In the examples, polylactic acid (NatureWorks® 4032D), L-alanine (Merck co.), carbon fiber (TAIRYFIL® CS-2516), carbon black (CABOT® XC-72), glass fiber (TAIWANGLASS GROUP 188), and coupling agent (ShinEtsu KBM-503) are used. The relative amounts of each component are shown in Tables 1 and 3.

[0035] PLA and L-alanine are uniformly mixed to prepare a first mixture. Components (c) and (d) are mixed to prepare a second mixture. The second mixture is added to the first mixture to prepare a PLA resin composition. The PLA resin composition is kneaded using a twin-screw extruder at a temperature range of about 160°C to about 195°C, and subsequently injected using an injection molding machine at a temperature range of about 150°C to about 200°C to form a tray.

[0036] Test the properties of each pallet according to the ASTM methods described in Tables 2 and 4, and record the results in Tables 2 and 4.

[0037] Table 1

[0038]

[0039] Table 2

[0040]

[0041] Given Comparative Examples 4 and 5, the use of a nucleating agent increases the HDT of the PLA product from about 52°C to about 130°C. Due to the support of the filler, Examples 1 to 3 have an HDT higher than about 130°C (here, about 134°C or higher) and exhibit improved mechanical properties (tensile strength, impact strength, flexural strength, and flexural modulus) compared to Comparative Examples 4 and 5. Notably, the impact strength of Examples 1 to 3 is about 1.88 to about 1.95 kg-cm / cm, significantly higher than the impact strength of Comparative Examples 4 and 5 (about 1.35 and about 1.21 kg-cm / cm, respectively).

[0042] The surface resistivity of Examples 1 and 2 is approximately 1.5 × 10⁻⁶. 3 With 4.7×10 4The surface resistivity of the PLA tray is significantly lower than that of Example 3 and Comparative Examples 4 and 5, indicating that the use of carbon fiber can further improve the antistatic properties of the PLA tray.

[0043] Table 3

[0044]

[0045] Table 4

[0046]

[0047] Examples 1, 6, and 7 have the same composition, but the amount of inorganic filler is changed to approximately 30 parts by weight, approximately 10 parts by weight, and approximately 5 parts by weight, respectively, based on approximately 100 parts by weight of PLA resin. Example 7, using approximately 5 parts by weight of filler, also achieves similar effects to Examples 1 to 3—improved mechanical properties, HDT, and reduced surface resistivity. When the amount of filler is approximately 10 parts by weight or more (Examples 1 and 6), the properties of the PLA tray can be further improved, such as an HDT higher than approximately 135°C and an impact strength higher than approximately 1.8 kg-cm / cm. Overall, the PLA trays manufactured in Examples 1 to 3, 6, and 7 all have suitable HDT, mechanical properties, and reduced surface resistivity, making them suitable for the electronics industry, such as in IC trays.

[0048] As used herein and unless otherwise defined, the terms “substantially,” “approximately,” “about,” and “approximately” are used to describe and take into account minor variations. When used in conjunction with an event or situation, the terms may cover situations where the event or situation occurs precisely or very close to occurring. For example, when used in conjunction with a numerical value, the terms may cover a range of variation less than or equal to ±10% of the value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. For example, if a first value is within a range of variation less than or equal to ±10% of a second value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%, then the first value may be “substantially” the same as or equal to the second value.

[0049] Unless the context clearly specifies otherwise, as used herein, the singular terms “a / an” and “the” may include multiple indicators.

[0050] Quantities, ratios, and other numerical values ​​are sometimes presented in range format in this document. It is understood that such range format is for convenience and brevity and should be flexibly interpreted to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or subranges covered within the range, as if each numerical value and subrange were explicitly specified.

[0051] Although the invention has been described and illustrated with reference to specific embodiments thereof, such description and illustration are not limiting. It will be readily understood by those skilled in the art that various changes can be made and equivalent elements can be substituted within embodiments without departing from the true spirit and scope of the invention as defined by the appended claims. Illustrations need not be drawn to scale. Differences may exist between artistic representations of the invention and actual devices due to variables such as manufacturing processes. Other embodiments of the invention may exist that are not specifically described. This specification and drawings should be considered illustrative rather than restrictive. Modifications may be made to adapt particular circumstances, materials, compositions, methods, or processes to the objectives, spirit, and scope of the invention. All such modifications are intended to be within the scope of the appended claims. Although the methods disclosed herein have been described with reference to specific operations performed in a particular order, it will be understood that these operations may be combined, subdivided, or rearranged to form equivalent methods without departing from the teachings of the invention. Therefore, unless specifically indicated herein, the order and grouping of operations are not limitations of the invention.

Claims

1. A polylactic acid resin composition comprising: 100 parts by weight of polylactic acid resin; Based on 100 parts by weight of the polylactic acid resin, 0.001 to 3 parts by weight of the nucleating agent; and Based on 100 parts by weight of the polylactic acid resin, 3 to 50 parts by weight of filler, wherein the filler comprises (1) carbon fiber, carbon black, or (2) a combination thereof, the resulting molded article having the following characteristics: a heat distortion temperature (HDT) of 134°C or higher as measured under a load of 264 psi according to ASTM D-648, and an average length of the carbon fiber of about 0.01 mm to about 800 mm.

2. The polylactic acid resin composition according to claim 1, wherein the nucleating agent comprises metal carbonates, ester derivatives of citric acid, metal silicates, amino acids, poly(amino acids), heterocyclic organic compounds, metal oxides, or combinations of two or more thereof.

3. The polylactic acid resin composition according to claim 1, wherein the filler is an inorganic filler.

4. The polylactic acid resin composition according to claim 1, wherein the resulting molded article has the following characteristics: a surface resistivity of 10 Ω·cm as measured according to ASTM D-257. 12 ohm / sq or less.

5. The polylactic acid resin composition according to claim 1, wherein the filler has a diameter of 0.01 μm to 100 μm.

6. The polylactic acid resin composition according to claim 1, wherein the resulting molded article has the following characteristics: a heat distortion temperature (HDT) between 134°C and 155°C under a load of 264 psi according to ASTM D-648.

7. The polylactic acid resin composition according to claim 1, further comprising 0.001 to 5 parts by weight of a coupling agent based on 100 parts by weight of the polylactic acid resin, said coupling agent comprising a silane coupling agent, a titanate coupling agent, or a combination thereof.

8. The polylactic acid resin composition according to claim 7, wherein the coupling agent comprises 3-acryloyloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, or a combination thereof.

9. A tray for use with electronic components, comprising: 100 parts by weight of polylactic acid resin; Based on 100 parts by weight of the polylactic acid resin, 0.001 to 3 parts by weight of the nucleating agent; and Based on 100 parts by weight of the polylactic acid resin, 5 to 30 parts by weight of filler, wherein the filler comprises carbon fibers and carbon black, the carbon fibers having an average length of about 0.01 mm to about 800 mm. The pallet described therein has the following characteristics: a heat distortion temperature (HDT) of 134°C or higher, measured under a load of 264 psi according to ASTM D-648.

10. The tray according to claim 9, further comprising 0.001 to 5 parts by weight of coupling agent based on 100 parts by weight of the polylactic acid resin.

11. The pallet according to claim 9, having the following characteristics: an impact strength of 1.5 kg-cm / cm or higher as measured by ASTM D-256; and a surface resistivity of 10⁻⁶ as measured by ASTM D-257. 12 ohm / sq or less.

12. A biodegradable molded article comprising: 100 parts by weight of polylactic acid resin; Based on 100 parts by weight of the polylactic acid resin, 0.001 to 3 parts by weight of the nucleating agent; and Based on 100 parts by weight of the polylactic acid resin, 5 to 30 parts by weight of filler, wherein the filler comprises (1) carbon fiber, carbon black, or (2) a combination thereof, wherein the carbon fiber has an average length of about 0.01 mm to about 800 mm. The molded articles described therein have the following characteristics: a heat distortion temperature (HDT) of 134°C or higher, measured under a load of 264 psi according to ASTM D-648.

13. The biodegradable molded article according to claim 12, wherein its decomposability after 90 days is at least 70 wt%.

14. The biodegradable molding article of claim 12, wherein the molding article is a tray for use in electronic components.

15. The biodegradable molded article of claim 12, wherein the filler further comprises carbon fiber, glass fiber, or a combination of two or more thereof.

16. The biodegradable molded article of claim 12, having the following properties: an impact strength of 1.5 kg-cm / cm or higher as measured by ASTM D-256; and a surface resistivity of 10⁻⁶ as measured by ASTM D-257. 12 ohm / sq or less.